Back Cover: Solvent‐Vapor‐Induced Reversible Single‐Crystal‐to‐Single‐Crystal Transformation of a Triphosphaazatriangulene‐Based Metal–Organic Framework (Angew. Chem. Int. Ed. 4/2020). Issue 4 (10th December 2019) - Nakatsuka, Soichiro; Watanabe, Yusuke; Kamakura, Yoshinobu; Horike, Satoshi; Tanaka, Daisuke; Hatakeyama, Takuji
Abstract : A new triphosphaazatriangulene, a hydrophobic extended π‐conjugated framework surrounded by hydrophilic phosphinate groups, is reported by T. Hatakeyama and co‐workers in their Communication on page 1435. This amphiphilic compound enables a solvent‐vapor‐induced reversible single‐crystal‐to‐single‐crystal transformation between a 3D‐MOF with reversible MeOH‐sorption characteristics and a 1D‐columnar assembled material with high proton conductivity.